2019
DOI: 10.3390/app9050896
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early Performance of Cement Paste by Low Field NMR

Abstract: The change of the evaporable water content in the early hydration process of cement paste with different water-to-cement ratios was monitored by low field nuclear magnetic resonance (LF-NMR) relaxometry. The hydration degree and gel/space ratio were accordingly calculated and analyzed. The test results show that the first derivative curves of the transverse magnetization are in good agreement with the known five stages of cement hydration process at an early age. The initial and final setting times of the ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…hydration of the cement, formation and distribution of hydration products, and the homogeneity of the cement paste [29][30][31][32][33]. LF-NMR is a noninvasive and nondestructive quantitative technique that provides valuable information on hydration kinetics, porosity, and pore size distribution [27], and has been used in cement and concrete research for many years [34,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…hydration of the cement, formation and distribution of hydration products, and the homogeneity of the cement paste [29][30][31][32][33]. LF-NMR is a noninvasive and nondestructive quantitative technique that provides valuable information on hydration kinetics, porosity, and pore size distribution [27], and has been used in cement and concrete research for many years [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, cement paste is composed of four phases: cement paste, surface products (products deposit on unreacted cement particles such as C-S-H), pore products (polycrystalline phases form in the water-filled pore space between cement particles such as calcium hydroxide), and capillary pores [23]. To follow the phases and the structural network changes in Portland cement caused by the addition of accelerators, several techniques can be used, such as X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX), and low-field nuclear magnetic resonance relaxometry (LF-NMR) [24][25][26][27][28][29][30][31][32][33][34][35][36]. XRD is a nondestructive material characterization technique for studying the fine structure of matter, and is successfully used as an alternative to other techniques for studying hydration compounds and quantitative crystalline phases [24][25][26][27][28].…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…According to ref. [ 46 , 48 ], high w/c dilutes the OH − and Ca 2+ ions in the cement paste, thus delaying the reaction rate of hydration. At the end of monitoring, the signal intensity of WC05-D-C25 still maintains a decreasing trend, while the decreasing trend of the curve of WC03-D-C25 has diminished.…”
Section: Resultsmentioning
confidence: 99%
“…Their results indicated that the heat treatment made it more difficult for the wood to be accessed by moisture, providing a scientific basis for assessing the application of heat-treated wood, especially for outdoor applications. In [2], the authors use low field relaxometry to monitor the change of the evaporable water content in the early hydration process of cement paste, with different water-to-cement ratios. Their results demonstrated that the first derivative curves of the transverse magnetization were in agreement with the known five stages of cement hydration process.…”
Section: Applications Of Low Field Magnetic Resonancementioning
confidence: 99%